A social program for adolescent and young adult survivors of pediatric brain tumors: The power of a shared medical experience. Issue 6 (1st November 2016) - Liptak, Cori; Brinkman, Tara; Bronson, Amanda; Delaney, Brian; Chordas, Christine; Brand, Sarah; Patenaude, Andrea Farkas; Muriel, Anna C.; Manley, Peter
ABSTRACT: Survivors of pediatric brain tumors experience several medical and psychosocial late effects including deficits in social competence. This mixed methods study investigated the experience of 19 adolescent and young adult survivors of pediatric brain tumors and 17 parents who participated in a social support program. Qualitative results demonstrated a significant social isolation that was compounded by medical late effects. Survivors perceived social support and acceptance from interactions with peers who have similar medical backgrounds as a key aspect of the group experience. Parents reported increased social confidence among survivors, although they did not report that social gains generalized beyond the group setting. Interventions to promote the transfer of specific social skills are needed.